Chemometric analysis and quantitative determination of Fici Microcarpae Folium from different geographical regions by HPLC-DAD. Issue 9 (15th June 2021) - Wang, Xinyu; Wei, Xiaohan; Tang, Qingfa; Huang, Wei Zhong; Teng, Yunxia; Liao, Zhizhong; Tan, XiaoMei; Mao, Xin; ,
Abstract: Fici Microcarpae Folium, the leaves of Ficus microcarpa, is commonly used for the treatment of influenza, chronic bronchitis, and tonsillitis in Traditional Chinese Medicine (TCM). Ficus microcarpa is mainly distributed in Guangdong and Guangxi provinces. The composition of herbal medicines can be easily affected by geographical regions, the quality control of FMF is essential. In this study, the high-performance liquid chromatography (HPLC) coupled with diode array detection (DAD) was developed to obtain a chromatographic fingerprint of Fici Microcarpae Folium from different geographical regions. Meanwhile, the contents of eight compounds of Fici Microcarpae Folium were determined. Principal component analysis (PCA), hierarchical cluster analysis (HCA), and orthogonal partial least squares discrimination analysis (OPLS-DA) were employed to evaluate the HPLC fingerprint. The results showed that the main compositions of Fici Microcarpae Folium from different geographical origins had no difference. The content of the main compositions was different, from which the peak 8, 15, 12, 11, 16, 3, and 21 were the main components that contribute to the difference. Isovitexin, vitexin, and isoorientin were the main components reflecting the quality of Fici Microcarpae Folium. This research could contribute to the quality control of Fici Microcarpae Folium. Graphical Abstract: UF0001